PENGARUH KECERDASAN EMOSIONAL TERHADAP KEPUASAN KERJA PADA KOPERASI KARYAWAN PT. TELKOM SIPORENNU MAKASSAR - Nurjaya, Nurjaya (Jurnal Minds: Manajemen Ide dan Inspirasi, 2015)
The objectif of this research to examine the effect of emotional intelegence toward job satisfaction at Koperasi Karyawan PT. Telkom Siporennu Makassar. The research uses 35 respondent of 35 members of population. The data were analyzed by linier regretion. The results stated independent variables there were positive and significantly influence toward job satisfaction.